Phytochemical Variability and Biological Activity in Echinacea Phytomedicine Help Manage Issues and Improve Germplasm - Rehan Haider; Geetha Das (MultiTech Publisher, 2023)
Diverse phytochemical compounds derived from the Echinacea plant have received extensive attention because of their potential biological and medicinal applications. Echinacea-based merchandise is extensively used to enhance the immune system and alleviate various ailments. This summary delves into the high-quality phytochemical varieties present in Echinacea species and highlights their associated biological activities. The healing capability of Echinacea stems from its diverse array of bioactive compounds, including alkamides, caffeic acid derivatives, polysaccharides, and flavonoids. These compounds have immunomodulatory, antioxidant, and antiviral properties. Therefore, Echinacea has been the subject of extensive research to understand its mechanisms of action and its potential scientific applications. However, the efficacy and quality of Echinacea-derived products face challenges associated with optimal manipulation and germplasm improvement. Ensuring regular tiers of bioactive compounds throughout unique batches of merchandise and addressing the issues of adulteration are vital for dependable therapeutic outcomes. Additionally, the genetic variability among Echinacea species provides hurdles in retaining consistent phytochemical profiles, making germplasm development urgent. Therefore, interdisciplinary efforts are required to address these challenges. Advanced analytical techniques, which include excessive-performance liquid chromatography and mass spectrometry, enable the specific quantification of the bioactive components of Echinacea. Molecular biology equipment is a resource for characterizing genetic diversity and identifying the key biosynthetic pathways. These improvements pave the way for better management protocols and targeted breeding strategies to enhance the Echinacea germplasm.